Factors Associated with Umbilical Venous Catheter Malposition in Newborns: A Tertiary Center Experience - Soonsawad, Sasivimon; Kieran, Emily A.; Ting, Joseph Y.; AlonsoPrieto, Esther; Panczuk, Julia K. (American Journal of Perinatology, 2021)
Objective Umbilical venous catheters (UVC) are widely used in neonatal intensive care (NICU). Noncentral catheter position is known to be associated with multiple adverse complications; however, risk factors for catheter malposition are unclear. This work aimed to identify clinical risk factors and complications associated with UVC malposition in neonates admitted in an NICU.Study Design A retrospective chart review was performed of inborn babies admitted to BC Women's Hospital NICU with UVC inserted in their first 7 days between July 2016 and June 2018. Infant and maternal demographic, radiograph, UVC-related data, and complications were reviewed.Results A total of 257 infants had UVC placed; 158 (61%) and 99 (39%) were in central and noncentral positions after initial placement, respectively. Of initially central-placed UVCs, a further 35 (22%) were pulled back or migrated to malposition on follow-up X-ray. Multivariable logistic regression analysis revealed the use of larger UV (5 Fr) catheter (odds ratio [OR]: 2.5, 95% confidence interval [CI]: 1.1–5.6, p = 0.026) and escalation of respiratory support mode (OR: 1.7, 95% CI: 1.0–2.8, p = 0.049) as significant predictors of catheter malposition.Conclusion Noncentral UVC position as well as migration were common after initial placement in this cohort. The use of larger size UV catheters and increasingly invasive respiratory support were risk factors associated with higher incidence of UVC malposition. Ongoing surveillance of UVC position is thus recommended.Key Points
Keywords: umbilical venous catheter; newborn; malposition; risk factors